a comparative analysis of canthal index of ekowe indigenes, bayelsa state (World Journal of Current Medical and Pharmaceutical Research, 2021)
Human body parts are useful in the predictive study of the unknown. The aim of this study is to know the normative values of the canthi of the Ekowe people. Measurements such as inner and outer canthal distances were carried out. The mean value of the innercanthal distance for males and females are 3.55±0.58 and 3.43±0.52. The mean outer canthal distance for male and female is 13.91±0.84 and 13.62±0.76. The canthal index for male and female is 25.59±4.54 and 25.30±4.03. Sexual dimorphism exists and statistical significant difference was noticed in the outer canthal distance between the males and females (P˂0.05). This study has provided us with normative reference values of inner and outer canthal distances and canthal index for the Ekowe Population which is import to the health care givers, Anatomist, ophthalmic industry and anthropologist